Development of a lateral move irrigation equipment for experimental plots - Eduardo de Castro Rocha, Francisco; Maria de Andrade, Lucilene; Antonio de Azevedo, Juscelino; Medrado da Silva, Euzébio; Mauro Folle, Sergio; Alberto Bento Fraz, Cláudio; Carlos Gomes, Antônio (Pesquisa Agropecuaria Brasileira, 1998)
A lateral move irrigation prototype for experimental plot was developed and tested at Embrapa-Centro de Pesquisa Agropecuária dos Cerrados (CPAC). This equipment includes two parts: module I and module II. The module I is the mobile part that is responsible for the water application through the lateral tubes with sprayers. The module II is the fixed part that is responsible for pulling and speed controlling of the module I. The equipment was tested operating with and without water, across a 150 m long route. It was observed a side movement of the module I, mainly at the beginning and at the end of the route, i. e., between 0 and 25 m and after 125 m. This result was due to the plot slope and to the way the steel cable was fitted around the module II drum. However, after fitting the wheels into soil furrows, there was no lateral deviation at all. As module I became closer to module II, the demand for traction power was increased, from 520 to 711 N, when the equipment worked without water, and from 525 to 1280 N with water. There was no significant variation in speed for the module I at the 30; 60; and 90 m/h movement along the route, either with or without spraying water.